2019
DOI: 10.20892/j.issn.2095-3941.2018.0290
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and gastric cancer risk: a comprehensive review synopsis from meta-analysis and genome-wide association studies

Abstract: Objective In the past few decades, more than 500 reports have been published on the relationship between single nucleotide polymorphisms (SNPs) on candidate genes and gastric cancer (GC) risk. Previous findings have been disputed and are controversial. Therefore, we performed this article to summarize and assess the credibility and strength of genetic polymorphisms on the risk of GC. Methods We used Web of Science, PubMed, and Medline to identify meta-analyses published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…An insufficient sample size of intestinal type may be responsible for the nonsignificant association between TFRC and GC in this study. Additionally, TFRC rs9846149 has not been investigated in relation to GC risk [ 17 ], and only 5% of participants were GG homozygous. Thus, further studies with a larger sample size are necessary to evaluate this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An insufficient sample size of intestinal type may be responsible for the nonsignificant association between TFRC and GC in this study. Additionally, TFRC rs9846149 has not been investigated in relation to GC risk [ 17 ], and only 5% of participants were GG homozygous. Thus, further studies with a larger sample size are necessary to evaluate this association.…”
Section: Discussionmentioning
confidence: 99%
“…In an environment without free iron, H. pylori will acquire iron from proteins, and TFRC will be used as an element for attachment and pathogenesis [ 15 ]. Single nucleotide polymorphisms (SNPs), which are the most common type of genetic mutation, may influence susceptibility to GC [ 17 ]. The effects of exposure to environmental factors may be modulated by genetic variants through the regulation of multiple biological pathways during gastric carcinogenesis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the IARC, H. pylori is considered as carcinogenic to humans (Group 1). A systematic review and meta-analysis [ 5 ] of published studies assessing the association of genetic factors with gastric cancer, described nine polymorphisms with significant association. Many of them were found using a candidate gene approach.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies assessing the role of polymorphisms in TLR2 , TLR4 , TLR5 , NOD1 and NOD2 in gastric cancer have been published. The associations of TLR4 rs4986790 (Asp299Gly) (minor allele frequency-MAF = 0.06) and rs4986791 (MAF = 0.04) were found to be statistically significant in meta-analyses [ 5 ]. The evidence for association of polymorphisms in TLR5 [ 17 ], NOD1 and NOD2 is scarce [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analysis support that single nucleotide polymorphisms may be used for the assessment of genetic predisposition to gastric cancer, with ethnicity, environmental factor and cancer subtype contributing to inconsistency in the results 5 . From among all molecular factors playing a role in progression from inflammation toward preneoplastic gastric lesions and cancer, recent research has focused on the possible influence of different type cytokine gene variants 6 . Recently, it was shown that cytokine gene variants are associated with susceptibility to different types of malignancy in a Romanian population 7 .…”
Section: Introductionmentioning
confidence: 99%